2020
DOI: 10.1101/2020.08.21.260620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inoculum effect of antimicrobial peptides

Abstract: The activity of many antibiotics depends on the initial density of cells used in bacteria growth inhibition assays. This phenomenon, termed the inoculum effect, can have important consequences for the therapeutic efficacy of the drugs, since bacterial loads vary by several orders of magnitude in clinically relevant infections. Antimicrobial peptides are a promising class of molecules to fight drug-resistant bacteria, since they act mainly by perturbing the cell membranes rather than by inhibiting intracellular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 95 publications
(140 reference statements)
1
8
0
Order By: Relevance
“…Therefore, these peptide therapeutics will need to be carefully evaluated in pre-clinical models like those presented in this work to help design appropriate treatment strategies. More generally, our results add to the growing body of evidence that show some of the challenges associated with quantifying the activity of peptide-based therapeutics 16,20 . However, given the new strategy shown here and also complementary tools being developed elsewhere 20 , it is hoped that these difficulties can be quantified and addressed at an early stage of development, facilitating the efficient clinical translation of this promising category of therapeutics.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, these peptide therapeutics will need to be carefully evaluated in pre-clinical models like those presented in this work to help design appropriate treatment strategies. More generally, our results add to the growing body of evidence that show some of the challenges associated with quantifying the activity of peptide-based therapeutics 16,20 . However, given the new strategy shown here and also complementary tools being developed elsewhere 20 , it is hoped that these difficulties can be quantified and addressed at an early stage of development, facilitating the efficient clinical translation of this promising category of therapeutics.…”
Section: Discussionsupporting
confidence: 55%
“…Cationic peptides also adsorb to surfaces of glass and plastic, leading to a loss of free peptides from solutions 19 ; this complicates experimental handling and may lead to inaccuracies in data interpretation in standard assays. A recent study by the Stella group confirmed a strong inoculum effect on the MICs of a range of antimicrobial peptides, which led the authors to question the utility of standard cellular screening assays for the field 20 . Other researchers have also identified a need for “new and standardized testing structures” to facilitate the translation of peptide antimicrobials from the bench to the clinic 16 .…”
Section: Introductionmentioning
confidence: 99%
“…We noticed that the protective effects of 2 μg/ml E. coli ATCC25922 OMVs and 20 μg/ml E. coli 08-85 OMVs in the growth curve assay were not exactly the same as in the killing protection assay. This could be due to the inoculum effect in which the initial density of cells affects the activity of many antibiotics including membrane-active peptides ( Loffredo et al., 2021 ). The growth curve assay was started with a 1:1,000 dilution of the overnight culture (starting inoculum of 10 5 CFU/ml), while the log-phase culture was used as the starting inoculum which was 10 7 CFU/ml in the killing protection assay.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the synergy factor obtained by comparing the MIC 50 values increases to 4.8 whereas it remains around 10 when the MIC 100 are considered. Because at very high inoculum the peptides distribute on many more cells it may be more difficult to reach a high enough density to kill ( 154 , 157 , 158 ). Thereby, one may speculate that at high cell density the increased binding affinity and the mesophase structures when the two peptides are added conjointly ( 69 ) help to reestablish local hot spots and synergy.…”
Section: Magainin 2—pgla Mixtures Show Synergistic Enhancement In Biological Assaysmentioning
confidence: 99%
“…This is also observed for the experimental series at a low CFU of 1.46 x 10 2 CFU/mL where the synergy factor by comparing the MIC 50 is 1.7 but again higher for the MIC 100 ( Figures 3A–C , so far unpublished data). However, it was recently pointed out that peptides also stick to surfaces of the test equipment thus the available concentration is probably significantly lower especially at low peptide concentrations ( 158 ).…”
Section: Magainin 2—pgla Mixtures Show Synergistic Enhancement In Biological Assaysmentioning
confidence: 99%